2022
DOI: 10.2147/ijgm.s385513
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Bone Morphogenetic Protein-9 is Decreased in Patients with Type 2 Diabetes and Non-Alcoholic Fatty Liver Disease

Abstract: Objective We aimed to examine the association between bone morphogenetic protein-9 (BMP-9) and type 2 diabetes mellitus (T2DM) in conjunction with non-alcoholic fatty liver disease (NAFLD) and insulin resistance (IR) and to identify evidence supporting the potential role of BMP-9 in the clinical prevention and treatment of T2DM in conjunction with NAFLD. Methods One hundred and twenty subjects were included in this study. We sorted all of the subjects into four groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…This was consistent with other studies. Xu et al found in middle-aged and older populations [ 23 ] as well as patients with T2DM and NAFLD [ 10 ], circulating BMP9 levels positively correlated with HDL and negatively correlated with markers of adiposity such as waist-to-hip ratio (WHR) or BMI, parameters of glucose metabolism (FPG and HbA1c) and TG. Animal studies also showed that upregulation of BMP9 levels inhibited the expression of lipogenic genes, ameliorated triglyceride accumulation in liver, decreased serum TC and TG [ 24 ], improved glucose tolerance, decreased FPG and alleviate IR in mice [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was consistent with other studies. Xu et al found in middle-aged and older populations [ 23 ] as well as patients with T2DM and NAFLD [ 10 ], circulating BMP9 levels positively correlated with HDL and negatively correlated with markers of adiposity such as waist-to-hip ratio (WHR) or BMI, parameters of glucose metabolism (FPG and HbA1c) and TG. Animal studies also showed that upregulation of BMP9 levels inhibited the expression of lipogenic genes, ameliorated triglyceride accumulation in liver, decreased serum TC and TG [ 24 ], improved glucose tolerance, decreased FPG and alleviate IR in mice [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with other studies. Xu et al found in middle-aged and older populations [23] as well as patients with T2DM and NAFLD [10], circulating BMP9 levels positively correlated with HDL and negatively correlated with markers of adiposity such as waist-to-hip ratio (WHR) or BMI, parameters of glucose metabolism (FPG and HbA1c) and TG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was consistent with other studies. Xu et al found in middle-aged and older populations [19] as well as patients with T2DM and NAFLD, [10] circulating BMP9 levels positively correlated with HDL and negatively correlated with markers of adiposity such as Waist-to-hip ratio (WHR) or BMI, parameters of glucose metabolism (FPG and HbA1c), and TG. Animal studies also showed that upregulation of BMP9 levels inhibited the expression of lipogenic genes, ameliorated triglyceride accumulation in liver, decreased serum TC and TG [20] , improved glucose tolerance, decreased FPG and alleviate IR in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al found circulating BMP9 decreased in patients with T2DM and NAFLD. [10] Our previous study [11] showed BMP9 was signi cantly reduced in NALFD mice, and supplement of BMP9 improved NAFLD by downregulating the expression of genes related to glucometabolism and lipometabolism, thereby reducing liver in ammation. All these ndings hint BMP9 has the potential as a serological biomarker and new treatment for NAFLD and MetS.…”
Section: Introductionmentioning
confidence: 96%